Avifaunal diversity of mangrove ecosystem, Kundapura, Udupi district, Karnataka, India - Vijaya Kumara2, K.M. Vijaya Kumar1* and (Recent Research in Science and Technology, 2011)
The avifaunal diversity and density of Mangrove Ecosystem, Kundapura, Udupi district, Karnataka, India, was studied for a period of one year from July-2010 to June-2011 based on observational methods. The mangrove ecosystem is inhabited by a variety of smaller birds, resident birds, migratory birds and wading birds. One of the most productive ecosystems of world is mangrove forests, providing shelter and feeding sites for many avifaunas. Mangrove and habitat estuaries are being used for various purposes like prawn culture, collection of shells for lime and harvesting of fish. Fluctuation of salinity of water and variations in food availability in different seasons affected the avifaunal diversity in the study area. This habitat attracted 32 bird species, belonging to the 19 families, which are residential, residential migrants and migratory including aquatic birds, waders and others. Highest number of egrets, common myna, open billed storks, black headed ibis and crows was recorded in three seasons, pre monsoon, monsoon and post monsoon. Other permanent residents were cormorants, pond herons, little herons and night herons.